Blood Pressure Response against Sedentary Lifestyle and Caffeine Ingestion in Population: A Cross Sectional Study - Hassan Raza, Maria Munir, Areeba Imran, Sadia Iram, Fasih Ahmed Hayat, Laraib Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coffee and tea mainly contain caffeine, and they are the most widely consumed beverages all over the world. The association between caffeine consumption and a sedentary lifestyle in the population is not homogeneous and remains inconsistent. Aims and objects: The aims and objectives of the current study were to examine the association of caffeine and an inactive lifestyle with blood pressure in the population. Conclusion: The present study concluded that there were significant (p≤0.05) changes in blood pressure among individuals in Group-Z compared to individuals in Group-X and Group-Y due to high caffeine intake. The results of this study demonstrated that high consumption of caffeine-containing food products increased both systolic and diastolic blood pressure in the population.